Ras–ERK Signaling in Behavior: Old Questions and New Perspectives - Fasano, Stefania; Brambilla, Riccardo (Frontiers in Behavioral Neuroscience, 2011)
The role of Ras-ERK signaling in behavioral plasticity is well established. Inhibition studies using the blood-brain barrier permeable drug SL327 have conclusively demonstrated that this neuronal cell signaling cascade is a crucial component of the synaptic machinery implicated in the formation of various forms of long-term memory, from spatial learning to fear and operant conditioning. However, abnormal Ras-ERK signaling has also been linked to a number of neuropsychiatric conditions, including mental retardation syndromes (“RASopathies”), drug addiction and L-DOPA induced Dyskinesia (LID). The work recently done on these brain disorders has pointed to previously underappreciated roles of Ras-ERK in specific subsets of neurons, like GABAergic interneurons of the hippocampus or the cortex, as well as in the medium spiny neurons of the striatum. Here we will highlight the open questions related to Ras-ERK signaling in these behavioral manifestations and propose crucial experiments for the future.